Spaces, times and environments that respect children’s culture - Villarroel Ambiado, Karina Alejandra; Magdalena Acuña, Paula (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
The educational experience unfolds in everyday living and in relationships with others and with the environment. Spaces, times, and environments reveal the visible and invisible, the tangible and intangible aspects of pedagogical practice. Behind every decision in configuring these elements, educational teams communicate their understandings of childhood. This article is the result of reflective practice, developed through the accompaniment of adult educators who seek to promote playful learning environments that respect the individuality and agency of children. From this perspective, this reflective article explores the meaning of educational environments, understood as cultural and relational constructions that support children’s well-being, exploration, and participation.